Central and peripheral arterial stiffness in patients after surgical repair of tetralogy of Fallot: implications for aortic root dilatation. Issue 12 (14th June 2006) - Cheung, Y F; Ou, X; Wong, S J
Abstract : Objectives: To test the hypotheses that (1) the central conduit arteries stiffen preferentially over the peripheral conduit arteries in patients with repaired tetralogy of Fallot (ToF); and (2) central arterial stiffening is related to aortic root dilatation. Design and patients: Heart–femoral pulse wave velocity (PWV), femoral–ankle PWV, carotid augmentation index and body surface area-adjusted aortic sinotubular dimension were determined in 31 children after ToF repair and compared with those in 31 age-matched controls after left-to-right shunt repair. In addition, the PWVs and augmentation index were related to the sinotubular junction dimension. Settings: Tertiary paediatric cardiac centre. Results: Compared with controls, patients had significantly greater heart–femoral PWV (mean 666 (SD 151) v 587 (81) cm/s, p = 0.021) and carotid augmentation index (−14.1 (17.0)% v −25.2 (14.6)%, p = 0.016), whereas the right (888 (202) v 845 (207) cm/s, p = 0.42) and left (918 (227) v 851 (215) cm/s, p = 0.25) femoral–ankle PWVs were similar between the two groups. The sinotubular junction z score of patients was significantly greater than that of controls (4.7 (1.5) v 1.1 (1.4), p < 0.001). Univariate analysis showed that the sinotubular junction z score correlated positively with heart–femoral PWV (r = 0.43, p = 0.001) and carotid augmentation index (r = 0.46, p = 0.001). Multiple linear regression similarly identified heart–femoral PWV (β = 0.30, p = 0.04) and carotid augmentation index (β = 0.31, p = 0.04) (model R 2 = 0.26) as significant determinants of sinotubular junction z score. Conclusions: The aorta stiffens in patients with repaired ToF, which may contribute to progressive dilatation of the aortic root in the long term.